Efektivitas Pelayanan Program Identitas Kependudukan Digital (IKD) pada Dinas Kependudukan dan Pencatatan Sipil Kota Malang: Effectiveness of Digital Population Identity (IKD) Program Services at the Population and Civil Registration Office of Malang City - Suprojo, Agung; Rena, Maria Florentina; Rohman, Abd. (Anterior Jurnal, 2025)
Digital Population Identity (IKD) is the key to improving the efficiency and quality of administrative services. The problem is that the achievement of activation and use of IKD in Malang City is very low. The urgency of the study was to determine the effectiveness of IKD services in Malang City. Informants were determined using a purposive sampling technique consisting of 1 Head of the Population ADB, 1 First Expert Population Database Administrator, and 3 community service users. Data were collected through in-depth interviews, direct observation, and documentation in the form of images and archives and then data analysis was carried out using an interactive model. The findings of the study were that the Malang City IKD Program service was generally effective. This can be concluded from the four variants used to measure the effectiveness of IKD services, namely target accuracy, program socialization, program objectives, and program monitoring. Of the four variants, all were implemented optimally. The effectiveness of the IKD program service has not been directly proportional to the expected output because the IKD activation target until early 2024 was 160 thousand, but only 64 thousand were activated as of April 2024. Supporting factors for IKD are clear policies, ready infrastructure, and competent and trained officers. The inhibiting factors are the varying levels of technological literacy in the community, the activation process that cannot be done independently, the limitations of mobile devices that are not compatible with installing the IKD application, and the community's apathy.